PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INERVENING PADA HONDA GAJAH MOTOR BYPASS PADANG - Reza; Neldi, Mondra; Charli, Chintya Ones (Jurnal Pijar, 2024)
This research aims to determine the influence of leadership and work environment on employee performance with job satisfaction as an intervening variable at Honda Gajah Motor Baypass Padang. The method used is structural equation modeling (SEM) analysis with partial least squares (PLS). By distributing a questionnaire to 40 respondents. The research results obtained are: 1) There is a positive and significant influence between Leadership and Job Satisfaction at PT. Honda Gajah Motor Bypass. 2) There is a positive and significant influence between the Work Environment and Job Satisfaction at PT. Honda Gajah Motor Bypass. 3) There is a positive and significant influence between Leadership on Employee Performance at PT. Honda Gajah Motor Bypass. 4) There is a negative and insignificant influence between the work environment on employee performance at PT. Honda Gajah Motor Bypass. 5) There is a negative and insignificant influence between Job Satisfaction and Employee Performance at PT. Honda Gajah Motor Bypass. 6) Job satisfaction does not mediate leadership on employee performance. 7) Job Satisfaction does not mediate the Work Environment on Employee Performance.